The Dialogue study: Protocol for a randomized clinical trial evaluating the efficacy of virtual reality-based psychotherapy plus treatment as usual versus treatment as usual for eating disorders. - Nina K Hansen; Emma S Ries; Thomas Ward; Valentina Cardi; Anne B Christensen; Carsten Hjorthøj; Merete Nordentoft; Nadia Micali; Louise B Glenthøj (PLoS ONE)
Background There is considerable interest in developing novel psychological interventions for eating disorders targeting characteristics potentially serving as maintaining factors in eating disorder pathology. An estimated 94% of patients with an eating disorder report a dominant internal voice commenting on weight and self-worth, often referred to as the 'eating disorder voice'. The experience of a more dominating 'eating disorder voice' has been linked to longer illness duration. Within psychotic disorders, an intervention termed AVATAR therapy, using computerized avatars, has proven effective in reducing the severity of the psychotic voice and the associated distress. Building on this evidence and the proof-of-concept for AVATAR therapy adapted to eating disorders, this study investigates an immersive version targeting eating disorder symptoms. In this adaptation participants engage with an avatar representing their inner eating disorder voice in virtual reality. Methods The study is designed as a randomized parallel-group superiority clinical trial. A total of 96 patients with an eating disorder will be allocated to either seven sessions of virtual reality-based avatar intervention plus treatment as usual (TAU) or TAU. All participants will be assessed at baseline, at treatment cessation (12 weeks), and at 24 weeks post baseline. A stratified block-randomization with concealed randomization sequence will be conducted. Discussion A case-series study has demonstrated that a non-immersive (2D) application of avatar-based therapy is feasible and acceptable for patients with an eating disorder. While this preliminary evidence is promising, further research is needed to evaluate the efficacy of an avatar-based intervention for eating disorders. This current study will be the first investigating this by testing a 3D immersive version of the intervention in a large-scale, methodologically rigorous trial. Should the efficacy of this intervention be confirmed, it could open new avenues for research into psychological treatments for eating disorders. Trial registration ClinicalTrials.gov NCT06345040.